IMPLEMENTASI MODEL PBL BERBANTUAN MEDIA INTERAKTIF WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI BALOK DAN KUBUS KELAS IV - Lestari, Fitri; Nursyahidah, Farida; Prasetyowati, Dina; Puspita Agustiani, Ika (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
To improve student learning outcomes, teachers should produce interesting Learning materials, such as interactive wordwall games, in response to the rapid advancements in technology during the 4.0 era. The objective of this research is to investigate strategies for enhancing the mathematical proficiency of fourth-grade students via the use of blocks and cubes. A total of 27 students from SDN Palebon 03 Semarang were included in this research, which used Classroom Action Research (PTK). PTK, or classroom action research, consists of two distinct stages. The researchers saw substantial gains in all areas when they used wordwall interactive media. The completion percentage for Cycle II was 92.59%, which is an increase over the 62.96% completion rate in Cycle I. Wordwall interactive media may enhance the learning outcomes of fourth graders in elementary school.